Educomunicação em perspectiva dialógico-discursiva: leituras do jornalismo político no ensino médio - Xavier, Manassés Morais (2018)
The present Doctoral Thesis, which is based on the concept of reading as a dialogical-discursive act, with responsible and responsive understandings, considering the relationship between the Dialogical Theory of Language (Bakhtin and the Circle) and Educommunication, consists of an action research carried out in a 2nd grade public high school class, in Campina Grande - PB. The research sustains the thesis that educomunicative activities, by following a dialogical-discursive perspective, allow the formation of critical-responsive readers, readers who build, in their media readings, senses from the perception of the verboideological nature of language. In this sense, the question which guided the present research was: what was the educational impact of political journalism readings, in the context of High School, for the construction of critical-responsive readers? In order to answer such question, the objectives were organized in: General - to analyze the perception of their points of view as well as their reading constructions concerning some political journalism texts related to the 2014 Elections for the Presidency of Brazil as well as for the Government of the State of Paraíba; and Specifics - to elaborate a DialogicalDiscursive pedagogical Didactic Plan for political media readings, based on the Dialogical Theory of Language and Educommunication; to describe and to analyze the impact of such readings on the formation of the students' political consciousness, as well as their evaluations regarding their participation in the political media project: do you do?; and to identify both the challenges and advances for the teacherresearch formation concerning this educomunicative intervention. As to the methodological procedures, the action research occurred from September up to November, 2014. The participating group was composed by 16 students, and the 12 face-to-face meetings were carried out weekly, with two hours class each. As to the research results, the analysis regarding the students’ readings allowed us to describe the educommunicative intervention impact concerning reading formation. In these terms, we point out an advance in the sense that the students, in their readings, perceived points of view and, from this perception, they could build their own points of view, and, this way, develop readings that enabled the presence of valuations, dialogical relations and critical positions. Such readings, with language marks, inscribed the students in discursive interaction processes. Among such marks, we can point out some declarative verbal expressions such as "I agree", "I believe", "we can see" – and comparisons among the different media communication vehicles concerning political parties ideological bias. The (non-final) considerations indicate how productive it is to invest in teaching methodologies when based on educommunication learning ecosystems, oriented by formative needs for reading practices aimed at exercising dialogical understanding, responsibly and responsively, in different discursive communication fields, among them, that one regarding to political journalism.